Persistent Headache from Pneumocephalus after Spinal Tumor Excision—A Case Report - Prachi Sharma; Sarika Juneja; Kavita Sandhu (Journal of Neuroanaesthesiology and Critical Care)
Pneumocephalus following spinal surgery is a rare but significant complication, particularly in procedures involving durotomy. Its nonspecific presentation can be mistaken for anesthesia-related effects, delaying diagnosis. We report a 70-year-old female who underwent D4 laminectomy and excision of a D3–D4 intradural extramedullary tumor. In the immediate postoperative period, she developed progressively worsening frontal headache and nausea, unresponsive to standard analgesia. A computed tomography scan on postoperative day 1 revealed pneumocephalus in the basal cisterns and Sylvian fissures. Despite no evident cerebrospinal fluid leak after watertight closure or intraoperative nitrous oxide use, factors such as subtle dural microleaks, intraoperative head elevation, and the use of a subfascial drain may have contributed to intracranial air entry. Vacuum activation of the drain, though not confirmed, could not be ruled out. Conservative management with supine positioning, oxygen therapy, analgesics, and early drain removal led to full symptom resolution. This case highlights the need for early recognition of pneumocephalus in patients with severe postoperative headache particularly as headache severity has been shown to correlate with the extent of pneumocephalus. Heightened awareness and preventive intraoperative strategies are essential to mitigate this risk.